Transperineal Versus Transrectal Magnetic Resonance Imaging-targeted Prostate Biopsy: A Systematic Review and Meta-analysis of Prospective Studies - Zattoni, Fabio; Rajwa, Pawel; Miszczyk, Marcin; Fazekas, Tamás; Carletti, Filippo; Carrozza, Salvatore; Sattin, Francesca; Reitano, Giuseppe; Botti, Simone; Matsukawa, Akihiro; Dal Moro, Fabrizio; Jeffrey Karnes, R; et al. (European urology oncology, 2024)
BACKGROUND AND OBJECTIVE: The benefits of the detection of clinically significant prostate cancer (csPCa) and safety of magnetic resonance imaging (MRI)-targeted transperineal (TP) prostate biopsy (TP-Tbx) versus transrectal (TR) approaches are still a matter of debate. This review aims to compare the efficacy and safety of TP-Tbx and MRI-targeted TR biopsy (TR-Tbx). METHODS: A systematic literature search was performed in PubMed/Medline, Scopus, and Web of Science to identify records of prospective randomized controlled trials (RCTs) comparing TP-Tbx and TR-Tbx published until May 2024. The primary outcomes included detection rates of csPCa (International Society of Urological Pathology [ISUP] ≥2) and rates of complications. KEY FINDINGS AND LIMITATIONS: Three RCTs (PREVENT, ProBE-PC, and PERFECT) met the inclusion criteria. The TR technique was commonly administered with antibiotic prophylaxis to mitigate infection risks or after a rectal swab. No difference was found between TP-Tbx and TR-Tbx in terms of either csPCa (odds ratio [OR] 0.9, 95% confidence interval [CI]: 0.7-1.1) or ISUP 1 prostate cancer (PCa; OR 1.1, 95% CI: 0.8-1.4) detection. Postprocedural infection (OR 0.8, 95% CI: 0.4-1.8), sepsis (OR 0.6, 95% CI: 0.1-4.5), and urinary retention rates (OR 0.5, 95% CI: 0.1-1.6) were similar. Pain during the TP approach was slightly higher than during the TR approach, but after 7 d of follow-up, the differences between the two approaches were minimal. Variations in biopsy numbers per patient, patient selection, use of 5-alpha reductase inhibitors, needle sizes, TP techniques, and pain scores (reported in only one RCT), along with the multicenter nature of RCTs, limit the study. CONCLUSIONS AND CLINICAL IMPLICATIONS: TP-Tbx and TR-Tbx show similar results in detecting PCa, with comparable rates of infections, urinary retention, and effectiveness in managing biopsy-associated pain. TP-Tbx can safely omit antibiotics without increasing infection risk, unlike TR-Tbx. The tendency to exclude from practice TR-Tbx with prophylactic antibiotics due to infection concerns could be moderated; however, the directionality of some key outcomes, as infections and sepsis, favor the TP approach despite a lack of statistical significance. PATIENT SUMMARY: There were no significant differences in the prostate biopsy approaches (transperineal [TP] vs transrectal [TR]) for prostate cancer detection and complications. However, the MRI-targeted TP prostate biopsy approach may be advantageous as it can be performed safely without antibiotics, potentially reducing antibiotic resistance.
Keywords: Randomized Controlled Trials as Topic; Magnetic Resonance Imaging; Prostate biopsy; prostata; Prostate; Prostate cancer; magnetická rezonance intervenční; Image-Guided Biopsy; Rectum; lidé; ultrazvukem navigovaná biopsie; magnetická rezonanční tomografie; Targeted biopsy; nádory prostaty; perineum; Prostatic Neoplasms; Transrectal; prospektivní studie; Male; Prospective Studies; Perineum; randomizované kontrolované studie jako téma; Magnetic Resonance Imaging, Interventional; Magnetic resonance imaging; mužské pohlaví; rektum; Transperineal; Humans